Study of titanium alloy Ti6242S oxidation behaviour in air at 560°C: Effect of oxygen dissolution on lattice parameters. (March 2020) - Berthaud, M.; Popa, I.; Chassagnon, R.; Heintz, O.; Lavková, J.; Chevalier, S.
Highlights: Oxidation of Ti6242S alloy at 560 °C in air follows a parabolic kinetics law. Oxide growth and oxygen dissolution kinetics obey to parabolic laws. Oxide scales are thin and mainly composed of rutile and anatase. Nitrogen enrichment of a thin layer in the metal. Oxygen dissolution in the metal results in lattice dilatation. Abstract: High temperature oxidation of titanium alloy Ti6242S was studied in air at 560 °C up to 10000 h. Oxidation kinetics obeys a parabolic law (kp = 8.7 × 10 −15 g². cm −4 .s -1 ). Oxygen dissolution in the metal was found to represent between 80 and 90% of the total mass gain. Thin oxide scales are mainly composed of TiO2, in top of which some alumina is present. Titanium nitride was detected as a very thin layer at the outer part of the metallic substrate. Underneath, the oxygen dissolution area was found to reach the maximum brittleness after 1000 h of oxidation.